APPLICATIONS OF COLOUR MODELS IN THE FOOD PROCESSING INDUSTRY: A SYSTEMATIC REVIEW - Manamohana K, Gururaj Bijur, Namesh Malarout, Babita Singla, S. Pavithra, Nithesh Naik (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Computer vision is an area that explores how machines can be rendered to obtain comprehension from visual videos or images. It is used widely in the field of food processing for quality grading and classification of food products. The acceptability of a food product by a consumer depends highly on its physical appearance. Colour, among other factors, is an important attribute that helps determine the quality of any food product. A colour model refers to an abstract mathematical model explaining how colours can be interpreted as number tuples, usually three or four values or colour components. This paper aims at reviewing the existing state of the literature on the applications of colour models in the food processing industry